Influence of flake thickness on flexural and moisture properties of wood cement panels fabricated from mixed furnish of eight hardwood species (2012)
The study was undertaken to investigate the influences of flake thickness on physical and mechanical properties of wood cement panel produce from mixed hardwoods species. The properties investigated are modulus of rupture (MOR), modulus of elasticity (MOE), water absorption (WA), thickness swelling (TS) and linear expansion (LE) of the experimental cement-bonded particleboards. Both the moduli MOR and MOE of specimens were calculated as specified in the ASTM Standard No D-1037 of 1978. MOR and MOE ranged from 6.04N/mm2 to 11.96 N/mm2 and 3110N/mm2 to 5060 N/mm2, respectively. Flake thickness had a significant effect on MOR and MOE at the 5% and 1% level of significance, respectively. Both cement/wood ratio and board density had a significant effect on MOR at the 1% level. Flake thickness was negatively and linearly correlated with MOR and MOE: On the other hand, cement/wood mixing ratio and board density were positively and linearly correlated with MOR and MOE. WA and TS tests for the study ranged from 34.60 to 44.04% and 0.57 to 1.61%, respectively. Analyses show that flake thickness, cement/wood mixing ratio, and board density had significant effects on WA and TS at the 1% level of significance. Results showed that WA and TS of the experimental panels increased as the thickness size of the particles increased from 0.250 to 0500mm.Two-way or three way significant interactions were not found to be significant between and among the three production variables applied in the experiment. The thinner the flakes used in board production, the stronger; stiffer and more dimensionally stable the cement-bonded particleboards.